Environmental Accounting Practices and Performance of Listed Sensitive Environmental Firms in Ghan - Amalo, Ajara (University of Cape Coast, 2020)
This research elucidates the relationship between environmental accounting practices and the financial outcomes of publicly traded firms with significant environmental impact in Ghana. Environmental accounting practices were evaluated through three distinct thematic lenses: energy management, water stewardship, and effluent and waste management, with Return on Assets serving as the metric for financial performance. The data was sourced from the annual reports and financial statements of ten publicly listed environmentally sensitive firms in Ghana. The analysis employed panel data regression techniques. The findings indicated a lack of statistically significant correlation between the scores of energy management, water management, and effluent and waste management on Return on Assets. Nevertheless, the variable of firm age exhibited a statistically significant positive correlation with Return on Assets. In light of these results, the study advocates for enhanced education of environmentally sensitive firms in Ghana by the Environmental Protection Agency and other regulatory organisations regarding the detrimental impacts of their operations on the environment and strategies to mitigate these issues through transparent reporting to stakeholders. Hence, helping Ghana to achieve the SDG agenda by the UN in 2030. Notwithstanding, firms engaged in environmental accounting practices must be motivated by the government with tax allowance to boost disclosure practices and compel other non-disclosing firms to do the same. Regulatory bodies should be resourced to strengthen the monitoring and enforcement of environmental accounting practices. Evidence of environmental accounting practices in academia is provided from this current study to Africa and the rest of the world.
x, 108p;, ill